Smart cities in India: Features, policies, current status, and challenges - Manoj Kumar, Nallapaneni; Goel, Sonali; Mallick, Pradeep Kumar (Institute of Electrical and Electronics Engineers Inc., 2018)
Smart cities are the modern urban concepts that are essential for people to have quality life. It is the conceptual view of grouping various technologies to attain smart and sustainable practices. This paper proposes the smart city definitions based on the general approach and the 3-C concept that defines the core character of the smart city. Moreover, this paper also presents a comprehensive study on the smart city concept in the view of India focusing on the features, selection and evaluation criteria, and policies. Besides these, present status, and challenges in the view of smart city in Indian context is also discussed.